Filial Gosudarstvennogo arkhiva Iaroslavskoi oblasti - Tsentr dokumentatsii noveishei istorii : putevoditel´ = Branch of the State Archive of the Yaroslavl Region - Center of Documentation of Modern History : guide-book - redkollegiia, S. A. Gvozdev (nauchnyi redaktor), L. V. Ganina, G. A. Kazarinova ; sostaviteli, O. V. Dolgova, G. A. Kazarinova (otv. sostavitel´) ... [et al.]. (Zven´ia, 2002)
Includes bibliographical references (p. 388-391) and index.